Arthur Grosvenor Daniells: from an Assistant to a Central Leader Seventh-day Adventist World Church - Doloksaribu, Yohanes Verdianto; Suciyanto, Suciyanto (Neolectura, 2024)
Arthur Grosvenor Daniells was a child who was born into a family that could be said to be less fortunate, he was even sent to an orphanage because of poverty, and together with his wife, Mary, he was once a servant in James White's family home. But in the end, Daniells became a pastor and even the longest-serving central leader of the Seventh-day Adventist Church (GMAHK) and was even recorded as one of the most reliable GMAHK administrators ever in GMAHK history. This article aims to find out Daniells’ theological and missiological journey so that he can become the leader of the global GMAHK center. This paper explains that in his spiritual journey, Daniells understood that the task of a pastor was not just shepherding, but rather evangelism. This was motivated by Jesus' Great Commission to spread the Gospel throughout the world, so that young Daniells began his missionary journey to New Zealand and Australia which would later lead him to become the leader of GMAHK in New Zealand and Australia, and even GMAHK worldwide. His principle of evangelism was to plan your work and work your plan, which proved effective in his missionary trips to areas he had never been before. This article is a qualitative approach that uses historical descriptive methods and documentary research. For each part, the researcher utilizes primary sources. Secondary sources are used only to see the current opinion about the issue.